PREPARATION OF 1-[18F]FLUORO-2-IODOETHANE AS A PROSTHETIC GROUP FOR [18F]FLUOROETILATION - Marcelle Vitória Carreira Dos Santos; Gabriela Viana de Souza; Helio Alexandre Stefani; Fabio Luiz Navarro Marques (Hematology, Transfusion and Cell Therapy)
Introduction/Justification: [18F]Fluorine is of considerable importance in radiochemistry for positron emission tomography (PET) due to its decay characteristics (18F; beta+ 96.7%, T1 = 2. 109:8 min). Numerous methods for introducing 18F into organic molecules have been developed, with alkylation being one of the methods. Thus, developing the radiochemistry process for the fluorination of dihaloalkyl compounds is a crucial step for the development of new radiotracers. Objectives: This work aims to prepare the 1-[18F]fluoro-2-iodo-ethane as a prosthetic group for radiolabeling amine or alcohol functionalized molecules, focusing on developing the radiotracers for molecular imaging. Materials and Methods: [18F]Fluoride was produced by the 18O(p,n)18F reaction on [18O]water using cyclotron (GE 16.5 MeV). Radiolabeling method 1: [18F]Fluoride was trapped in a QMA cartridge and released by eluting tetraethylammonium bicarbonate (TEAHCO3 (7.5 mg, 2.47 μmol) in methanol into a vial. The methanol solution was heated at 100oC with a gentle stream of N2 until methanol was evaporated. Acetonitrile (AcN) was added (0.5 mL × 2) and evaporated to complete drying the system. A solution containing 9 mg (3.19 μmol) of 1,2-diiodoethane in 0.5 mL AcN was added and heated at 100oC for 10 or 15 min. Radiolabeling method 2: Water solution containing [18F]fluoride was added to a vial and dried by azeotropic evaporation with acetonitrile (0.5 mL × 2) at 100 oC with a gentle stream of N2 over 10 min. An acetonitrile solution containing TEAHCO3 (7.5 mg, 2.47 μmol) or TBAHSO4 (8.3 mg, 2.47 μmol) was added and evaporated; finally, 9 mg (3.19 μmol) of 1,2-diiodoethane in 0.5 mL of AcN was added and heated at 100oC for 10 min. At the end of the reactions, vials were allowed to reach room temperature; a sample was removed and analyzed in TLC-SG and TLC-RPc18 using ethyl acetate or ethanol as the mobile phase. [18F]fluoride ion and [18F]fluoride/ammonium quaternary ion pair were also analyzed by TLC chromatography. Stripes were cut in segments of 1 cm and read in a well counter. Results: All the chromatographic systems evaluated presented [18F]fluoride and [18F]fluoride/ammonium quaternary retained in the origin of the systems. Samples of the reaction showed a radioactive product moving to the front of the TLC-RPc18 using ethanol, and this TLC system was used to analyze the reaction efficiency. Radiochemical yield was calculated considering the Rf 0.5-1.0 radioactive counts in the TLC-RPc18/EtOH. Reaction under condition 1: heating time: 10 min = 24.5%, 15 min = 10.6%. Reaction under condition 2: TEAHCO3 - 10 min = 47.6%, TBAHSO4 - 10 min = 24.8%. Conclusion: The results demonstrated the feasibility to produce 1-[18F]fluoro-2-iodo-ethane by both techniques, and heating time and kind of ammonium salt can influence the reaction yield. Directly adding [18F]fluoride to the vial, without using a QMA cartridge, seems to be a good alternative to optimize multiple reaction parameters in the radiolabeling process. This route will be used to optimize parameters for the proposed reaction and for other dihaloalkyl molecules.